The case for cash - James Joseph McAndrews (Asian Development Bank Institute (ADBI), 2017)
Cash is an extremely useful social contrivance. Two possible drawbacks of high-denomination cash have recently been discussed by Kenneth Rogoff in his book The Curse of Cash, and echoed by other economists. They are the extensive use of high-denomination cash by criminals and others engaged in illicit and corrupt activities, and the role that cash plays in avoiding deeply negative nominal interest rates imposed on bank accounts. Rogoff and others call for a phaseout of high-denomination cash over a long time. The use of cash in crime, I'll argue, is preferable to the alternative, and there are limits to the benefits of deeply negative nominal interest rates. There are no adequate alternatives to cash for poor and unbanked people. Consequently, the current high-denomination cash in the United States should be retained.
Keywords: E40; E50; 330; Economics; Finance sector development